World Livestock Disease Atlas : A Quantitative Analysis of Global Animal Health Data (2006-2009) - World Bank; TAFS Forum (World Bank, Washington, DC and TAFS Forum, Bern, 2017)
The authors have analyzed animal health data for the years 2006 through 2009 as reported by the World Organisation for Animal Health (OIE)-the four most recent 'World animal health yearbooks' available when the analysis was prepared. The data covers 176 countries and economies on 71 livestock diseases (30 zoonoses and 41 non-zoonotic diseases) and 8 species or groups of species (cattle, sheep and goat, swine, poultry, equidae, buffalo, cervidae, and camels). Losses due to death, destruction or slaughter were distinguished. In total, the scope of the analysis comprises about 2.7 million data points. On average, over the four years analyzed, the Islamic Republic of Iran, China, and Brazil lost the highest absolute numbers of Livestock Units (LSUs), while Israel, Iran, and Namibia suffered the highest losses relative to their livestock populations. Data need to be interpreted taking into account a potential reporting bias resulting from countries' different levels of reporting transparency and competency. This report is not based on the 'real' world animal health situation, but on the best information available to the authors.